Recent prints: landscape and still-life - Stack, Karin E., author; Dormer, James T., advisor; Orman, Jack L., committee member; Simons, Stephen R., committee member; Twarogowski, Leroy A., committee member; Ronda, Bruce A., committee member (Colorado State University. Libraries, 1998)
My investigations of the landscape are tied to observation but equally informed by memory and imagination. I am fascinated by creating light, space, and illusion, however, these interests are countered by my interest in formal qualities. I hope to achieve psychological impact and expressive effect while exploring isolation, emptiness, and disquietude in the landscape. I am attracted to the intaglio medium because of the richness of the resulting images as well as to the process itself. Initially, I work from observation, then generalize, edit and invent. I also explore still-life subjects using lithography in which I investigate compressed space and abstract shapes. I sometimes include ambiguously scaled houses within the still-life to evoke architectural space and present a question or tension.
Keywords: still life in art; Intaglio printing; Landscapes in art